Consumer Acatalepsy Towards Buying Behaviour for Need-Based Goods for Sustainability During the COVID-19 Pandemic - Kulshrestha, Dhiresh Kulshrestha; Tiwari, Muklesh Kumar; Shalender, Kumar; Sharma, Sandhir (Indian Journal of Marketing, 2022)
Purpose : The study aimed to examine the consumer acatalepsy towards buying behavior for need-based goods (NBGS) for sustainability during COVID-19 and behavioral intentions for NBGS using the framework of value – attitude – behavior in India. Design/Methodology/Approach : Using the extant literature review, the study developed a conceptual model describing consumers’ buying behavior and behavioral int entions related to NBGS. The research employed the hypo-deductive research design approach for carrying out the study. Findings : The study found that attitude, economic depression, subjective norms, perceived consumer effectiveness, availability of control, and buying intention were positively related to the buying behavior of consumers in the NBGS category. Research Limitations/Implications : The research offered new insights into academia and practice using instrumental values, terminal values, and consumer buying behavior. It is unique for providing a fresh perspective on the NBGS and consumer behavior in COVID-19 times. Practical Implications : As the study deep dived into the behavioral aspects of the consumers, it will help shape the attitude of market professionals to analyze the instrumental and terminal values thoroughly. The findings of the research will prove instrumental in more effective and efficient decision-making processes for need-based goods in the consumer market. Social Implications : At individual and social levels, values represent the guiding force that shapes human behavior. This study will help to extend the overall understanding related to consumer behavior in the domain of NBGS using the basis of value and its impact on the behavioral patterns of consumers. Originality/Value : In the context of NBGS, this research paper dealt explicitly with the behavioral factors related to instrumental and terminal values. The study is also unique in that it evaluates the various parameters related to consumers’ buying behavior in the NBGS category during COVID-19. Evaluating these factors makes the research unique and one of its kind in consumer behavior.